The possible involvement of granulysin mediated cytotoxicity in keratinocytes disruption in lichen planus. (April 2021) - Vičić, Marijana; Sotošek, Vlatka; Brajac, Ines; Kaštelan, Marija; Prpić-Massari, Larisa
Abstract: Lichen planus is a chronic mucocutanous disorder histopathologically characterized with a keratinocytes apoptosis, subsequent basal cell layer liquefaction and accumulation of the inflammatory infiltrate in papillary dermis. A formation of apoptotic bodies in basal cell layer is due to a cytotoxic lymphocyte attack to the basal keratinocytes. It has been demonstrated that the cytotoxic molecules included in this attack are perforin and granzyme B. Both molecules are found upregulated in CD8+ lymphocytes that are in close contact to keratinocytes. However, their amount is lower in lichen planus than in other skin disease characterized by liquefaction and vacuolar degeneration of the basal epidermal layer. This could speculate about other cytotoxic molecule such as granulysin that could mediate keratinocyte apoptosis. Therefore, in this article we hypothesize about the crucial role of granulysin molecule in keratinocytes killing that could contribute to a lichen planus pathogenesis.